Potential Analysis of 3D Printing Products in Surabaya - Michael Evan; Joniarto Parung (Jurnal Sistem Teknik Industri, 2023)
The cost reduction and production time reduction are the benefits of 3D printing in the manufacturing industry, which can be developed in printing casual shoes that meet customer needs. Although 3D Printing promises many benefits, many are still doubtful about its application in Indonesia. To examine the potential use of 3D printing in Indonesia, information was extracted about the knowledge of the Indonesian people about 3D printing machines and asking to potential investors for an assessment of 3D printing in Indonesia. Data collection was done through an online survey. Respondents were selected randomly with a purposive sampling technique. Survey results show that 91% of respondents said they already knew 3D printing machines, they also knew that there were various kinds of 3D printing products and various kinds of raw materials that could be used. Prospective investors will assess 3D printing products by taking into account market convenience, product uniqueness, workshop/shop location and availability of specialized human resources.